USING THE SUSTAINABLE BALANCED SCORE CARD AS A MODEL FOR COST MANAGEMENT TOOLS TO EVALUATE THE ORGANIZATIONAL PERFORMANCE OF INDUSTRIAL COMPANIESAPPLIED FIELD RESEARCH IN THE GENERAL COMPANY FOR RUBBER AND TIRE INDUSTRIES (World Economics and Finance Bulletin, 2024)
The nature of business institutions and organizations' work is competitive in accordance with ongoing developments in global markets, especially in the world of advanced manufacturing. It was necessary for business institutions and organizations to invent modern tools to conduct their work in line with these developments. Perhaps the most prominent of these tools that senior management relies on are cost management tools, which include a set of tools that help senior management achieve its goals. The most prominent of these tools is the balanced score card. The balanced score card aims to evaluate government institutions' organizational performance in the field of cost and administrative accounting based on a set of financial and nonfinancial indicators
Keywords: Cost Management Tools; Balanced Score Card; Sustainable Balanced Score Card